The Landscape of Virtual Reality Use in Mobility Rehabilitation from 2010–2023: A Scoping Review - Danielle T. Felsberg; Reza Pousti; Charlend K. Howard; Scott E. Ross; Louisa D. Raisbeck; Jared T. McGuirt; Christopher K. Rhea (Technologies)
Significant advancements in virtual reality (VR) technology have occurred in the past decade, allowing clinical researchers to take advantage of these reduced barriers to explore the use of VR in patient populations. This scoping review on VR interventions to improve mobility in adults and children focuses on the literature from 2010–2023. A total of 2736 articles were screened and 126 articles met the inclusion criteria. Most of the studies were conducted in inpatient clinical settings (n = 41) and investigated VR interventions to improve balance (n = 118). Less immersive (n = 108) products such as Nintendo Wii or Xbox Kinect were primarily used. Additionally, 37.0% of studies (n = 47) used off-the-shelf programs like Wii Fit Plus and 73.2% of studies (n = 93) found statistically significant improvements in motor outcomes following VR intervention. The articles included in this review suggest that the majority of VR research for physical rehabilitation is being performed in clinical settings. Most studies reported statistically significant improvements in their outcome variables following VR intervention. These observations demonstrate that research in this area is moving beyond proof-of-concept and toward translation to clinical applications.